White rage : the unspoken truth of our racial divide - Anderson, Carol (Carol Elaine) (New York : Bloomsbury, an imprint of Bloomsbury Publishing Plc, 2017)
"As Ferguson, Missouri, erupted in August 2014, with media commentators referring to the angry response of African Americans yet again as 'black rage,' historian Carol Anderson wrote a remarkable op-ed in the Washington Post showing that this was, instead, 'white rage' at work. 'With so much attention on the flames,' she writes, 'everyone had ignored the kindling.' Since 1865 and the passage of the Thirteenth Amendment, every time African Americans have made advances toward full participation in our democracy, white reaction has fueled a deliberate and relentless rollback of their gains. The end of the Civil War and Reconstruction was greeted with the Black Codes and Jim Crow. The Supreme Court's landmark 1954 Brown v. Board of Education decision was met with the shutting down of public schools throughout the South while taxpayer dollars financed segregated white private schools. The Civil Rights Act of 1964 and Voting Rights Act of 1965 triggered a coded but powerful response--the so-called Southern Strategy and the War on Drugs that disenfranchised and imprisoned millions of African Americans. Carefully linking these and other historical flash points when social progress for African Americans was countered by deliberate and cleverly crafted white opposition, Anderson pulls back the veil that has long covered punitive actions allegedly made in the name of protecting democracy, fiscal responsibility, or protection against fraud. Compelling and dramatic in the unimpeachable history it relates over a century and a half, White Rage will add an important new dimension to the national conversation about race in America"--
Prologue: Kindling -- Reconstructing Reconstruction -- Derailing the Great Migration -- Burning Brown to the Ground -- Rolling Back Civil Rights -- How to Unelect a Black President -- Afterword to the Paperback Edition. After the Election: Imagining.
Includes bibliographical references (pages 181-263) and index.
Keywords: African Americans -- Civil rights -- History; African Americans -- Politics and government; African Americans -- Social conditions; White people -- United States -- Attitudes -- History; White people -- United States -- Politics and government; Opposition (Political science) -- United States -- History; Racism -- United States -- History; African Americans -- Civil rights; African Americans -- Politics and government; African Americans -- Social conditions; Race relations